PENINGKATAN KINERJA SALURAN DRAINASE KOTA LANGSA BERDASARKAN PENATAAN RUANG - Alfiansyah Yulianur; Sugianto Sugianto; Eka Mutia (JURNAL TEKNIK SIPIL, 2013)
Abstract:Spatial planning of Langsa City is still required in order to realize clean city, neat and beautiful. Spatial planning can also improve performance of drainage channels so that flood and inundation do not occur. Gampong Teungoh village and Gampong Baru village is an area of development and entrance Langsa City from the east, that still occur floods and inundation of up to 0.3-0.5 m so that performance improvement of drainage channels is required. Drainage channel performance is good if the dimensions of channels enough to drain rainwater runoff.  Drainage performance was evaluated before and after spatial planning is done by comparing discharge or capacity of channel with discharge of flood design of rainwater runoff. Spatial planning is done by providing a green space area of 10 % of the land area of residential parcels, maintain the function of public green space that has been there, and make a parking lot out of the water absorptive material. After spatial planning is done, runoff coefficient decreased from 0.45-084 to 0.4-0.75 so that discharge of flood design of rainwater runoff also decreased. This is causes channel performance previously not good to be good. Then decreasing of this discharge also caused available of remaining land due to channel dimensions that smaller than before. In this remaining land was used as a green line that can reduce the value of the runoff coefficient and then reduce discharge of rainwater runoff, and ultimately may also impact the performance improvement of drainage channels.Keywords : spatial planning, performance, drainage channel, green space area, runoff coefficient, discharge storm water runoff.Abstrak:Penataan ruang Kota Langsa masih diperlukan demi mewujudkan kota yang bersih, rapi dan indah. Penataan ruang yang baik dapat juga meningkatkan kinerja saluran drainase sehingga banjir dan genangan tidak terjadi. Desa Gampong Teungoh dan Gampong Baru merupakan kawasan pengembangan dan kawasan entrance Kota Langsa dari arah Timur, yang . masih mengalami banjir dan genangan hingga mencapai 0,3-0,5 m sehingga diperlukan peningkatan kinerja saluran drainase agar banjir genangan tersebut tidak terjadi. Kinerja saluran drainase dikatakan baik jika dimensi saluran cukup untuk mengalirkan debit rencana limpasan air hujan. Kinerja saluran drainase dievaluasi sebelum dan sesudah penataan ruang dilakukan dengan membanding debit saluran dengan debit rencana. Penataan ruang dilakukan dengan menyediakan ruang terbuka hijau seluas 10% dari luas tanah persil rumah tinggal, tetap mempertahankan fungsi ruang terbuka hijau umum yang telah ada, dan membuat lahan parkir dari bahan serap air. Setelah penataan ruang, nilai koefisien aliran menurun dari 0,45-084 menjadi 0,4-0,75 sehingga debit rencana aliran limpasan air hujan juga menurun. Penurunan debit ini menyebabkan kinerja saluran yang sebelumnya tidak baik menjadi baik. Kemudian penurunan debit ini juga menyebabkan adanya sisa lahan akibat pengecilan dimensi saluran. Pada sisa lahan ini dijadikan jalur hijau yang dapat memperkecil nilai koefisien aliran dan kemudian memperkecil debit aliran limpasan air hujan, dan akhirnya dapat pula berdampak kepada peningkatan kinerja saluran drainase.